Fresno County Young Lawyers Association Halloween Dance at Crossland's Barn - Watkins, Howard::::::::: (1984)
Close up of Howard Watkins wearing Cherokee Indian headdress and Christine Watkins wearing Indian blue sari Howard's face with paint marks